Hubungan antara Insomnia dengan Konsentrasi Belajar pada Mahasiswa Program Studi Ilmu Kedokteran - Annisa Nurul Syafitri Salam; Dewi Rosiana (Bandung Conference Series: Psychology Science, 2022)
Abstract. Insomnia is a sleep disorder characterized by difficulty initiating sleep, finding it difficult to maintain sleep, or feeling dissatisfied with sleep. Symptoms due to insomnia that will be experienced for example feeling sleepy during the day, which can cause decreased learning concentration and disrupted daily activities. Concentration of learning is to focus a mind on a subject to the exclusion of all matters that have nothing to do with the lesson. Based on this phenomenon, the problems in this study are formulated as follows: (1) What is the picture of insomnia in medical science students in Bandung? (2) What is the picture of the concentration of learning in medical science students in Bandung City? (3) Is there a relationship between insomnia and learning concentration in medical science students in Bandung City?. Researchers use the method of correlational analysis techniques using a quantitative approach. The population selected in this study were students of the Bandung City medical science study program, amounting to 1,896 students. With the sampling technique, namely Qouta Sampling, the number of research samples obtained was 330 students. The data collection technique used in this study was a questionnaire. The data analysis technique used in this research is descriptive analysis technique. The results of this study are: There is a negative relationship between insomnia and learning concentration in students of medical science study program in Bandung City, and is included in the weak category of -.132. Abstrak. Insomnia adalah salah satu gangguan tidur yang ditandai dengan kesulitan untuk memulai tidur, merasa sulit untuk mempertahankan tidur, atau tidur yang terasa tidak puas. Gejala akibat insomnia yang akan dialami misalnya merasa ngantuk di siang hari, yang dapat menyebabkan konsentrasi belajar menurun dan aktivitas sehari-hari yang terganggu. Konsentrasi belajar adalah memusatkan sebuah pikiran pada sebuah mata pelajaran dengan mengesampingkan seluruh perihal yang tidak memiliki kaitan dengan pelajaran. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana gambaran insomnia pada Mahasiswa program studi ilmu kedokteran Kota Bandung? (2) Bagaimana gambaran konsentrasi belajar pada Mahasiswa program studi ilmu kedokteran Kota Bandung? (3) Apakah ada hubungan antara insomnia dengan konsentrasi belajar pada Mahasiswa program studi ilmu kedokteran Kota Bandung?. Peneliti menggunakan metode teknik analisis korelasional dengan menggunakan pendekatan kuantitatif. Populasi yang dipilih dalam penelitian ini adalah Mahasiswa program studi ilmu kedokteran Kota Bandung yang berjumlah 1.896 Mahasiswa. Dengan teknik pengambilan sampel yaitu Qouta Sampling diperoleh jumlah sampel penelitian sebanyak 330 Mahasiswa. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah kuesioner. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah teknik analisis deskriptif. Hasil dari penelitian ini adalah: Terdapat hubungan negatif antara insomnia dengan konsentrasi belajar pada Mahasiswa program studi ilmu kedokteran Kota Bandung, serta termasuk kategori lemah sebesar -.132.